DEVELOPMENT OF INTERACTIVE TEACHING MATERIALS THROUGH HEYZIN IN IMPROVING STUDENTS’ MATHEMATICAL LITERACY ABILITY - Khoirunnisa Berliananda Sukesi; Jusra, Hella (Department of Pendidikan Guru Madrasah Ibtidaiyah Universitas Islam Negeri Alauddin Makass, 2024)
Abstract The objective of this research is to develop interactive pedagogical resources on the Heyzin platform, employing Canva to enhance the Mathematical literacy competencies of students in the fourth grade. The Research and Development (R&D) method with the ADDIE model was used in this study to formulate interactive educational materials. This research integrated both qualitative and quantitative data. Qualitative data were acquired through interviews conducted with subject matter experts and media specialists. Conversely, quantitative data were derived from the analysis of pretest and posttest scores that evaluate mathematical literacy proficiency, in addition to student satisfaction surveys. The pretest and posttest results obtained an N-Gain with a moderate category. The results of the effectiveness test stated that there was an increase in Mathematical literacy through the use of interactive teaching materials developed through Heyzin. The results of the average increase indicate an increase that is classified as a moderate category. This study concludes that developing interactive teaching materials based on Canva through Heyzin can be an alternative learning method that is effective in improving students' Mathematical literacy.